Does intraperitoneal medical ozone preconditioning and treatment ameliorate the methotrexate induced nephrotoxicity in rats? - (:unkn) unknown (E-CENTURY PUBLISHING CORP, 2015)
Methotrexate is a chemotherapeutic agent used for many cancer treatments. It leads to toxicity with its oxidative injury. The purpose of our study is investigating the medical ozone preconditioning and treatment has any effect on the methotrexate-induced kidneys by activating antioxidant enzymes in rats. Eighteen rats were divided into three equal groups; control, Mtx without and with medical ozone. Nephrotoxicity was performed with a single dose of 20 mg/kg Mtx intraperitoneally at the fifteenth day of experiment on groups 2 and 3. Medical ozone preconditioning was performed at a dose of 25 mcg/ml (5 ml) intraperitoneally everyday in the group 3 and treated with medical ozone for five more days while group 2 was received only 5 ml of saline everyday for twenty days. All rats were sacrificed at the end of third week and the blood and kidney tissue samples were obtained to measure the levels of TNF-alpha, IL-1 beta, malondialdehyde, glutathione and myeloperoxidase. Kidney injury score was evaluated histolopatologically. Medical ozone preconditioning and treatment ameliorated the biochemical parameters and kidney injury induced by Mtx. There was significant increase in tissue MDA, MPO activity, TNF-alpha and IL-1 beta (P<0.05) and significant decrease in tissue GSH and histopathology (P<0.05) after Mtx administration. The preconditioning and treatment with medical ozone ameliorated the nephrotoxicity induced by Mtx in rats by activating antioxidant enzymes and prevented renal tissue.
Keywords: Kidney; medical ozone; preconditioning; methotrexate; nephrotoxicity; HUMAN-LEUKOCYTES; THERAPY; MYELOPEROXIDASE; INFECTION; INDUCTION; TOXICITY; EFFICACY; DISEASES; DAMAGE